Disentangling the Ecological Value of Tree Hollows to Wildlife Along Elevation Gradients: The Case of Southern Temperate Forests - Vergara-Egert, P; Quiroz-Espinoza, M; Fierro-Tapia, C; Moreira-Arce, D; Alaniz-Baeza, A; Carvajal-Leon, M; Zuñiga-Alvarez, A; Hidalgo-Corrotea, C (Elsevier B.V., 2024)
The ecological importance of tree hollows relies on environmental factors that influence microhabitat requirements for wildlife. Thus, the value of hollows as thermal microhabitats should increase with elevation, but understanding this phenomenon involves a separate assessment of hollow use and site occupancy. Here, we evaluated the use of tree hollows by vertebrates and invertebrates along elevational gradients in southern Chilean temperate forests. Camera trap and Bayesian models were used to analyze separately hollow use and site occupation. Four of seven invertebrate taxa and 21 of 25 vertebrate species used hollows. All lizard and mammal species (rodents, bats, kodkods, and opossums) were found using hollows, while 13 bird species (77 %) did it. The hollow occupation of only two species responded to elevation, with Chilean opossums being more likely to use hollows as elevation increased, while black-throated huet-huets exhibited the opposite pattern. Chucao and Magellanic tapaculos increased their occurrence probability as elevation increased while that of jewel and blue-bellied lizards increased with elevation. Giant bumblebees, austral thrushes, and Chilean opossums preferred hollows in evergreen (non-Nothofagaceae) tree species while huet-huets preferred hollows in Nothofagus trees. A strong positive association between hollow density and elevation was also found. These results suggest Chilean opossums benefit from using hollows at high altitudes due to their sensitivity to low temperatures while the lower availability of tree hollows at low altitudes causes black-throated huet-huets to be limited by hollows. Thus, wildlife conservation in these forests requires the maintenance of hollows in different tree species along elevational gradients. © 2024 Elsevier B.V.